The Effectiveness Of Waste Cooking Oil Recycling Project-Based Learning To Improve Students’ High Order Thingking Skills - Yeni Sarif; Noor Fadiawati; M. Mahfudz Fauzi Syamsuri (International Journal of Chemistry Education Research, 2019)
This study aimed to describe the effectiveness in project-based learning of waste cooking oil recycling to improving students’ high order thinking skills. The research design used was the The Matching-Only Pretest-Posttest Control Group Design. The population in this research was all of students in grade XI MIA one of Senior High School in Bandarlampung. The sample of the research was the students of class XI MIA 4 and XI MIA 6. The data analysis technique used was non parametric statistic test using Mann Whitney U to postestt value. The results of this study it can be seen from postest value. Postest value in the experiment class that is greater than the postest value in the control class as well as the <g> on the medium categorized in the experimental class and in the low control class indicate that project-based learning of waste cooking oil recycling can improve students' high order thinking skills. Keywords: high order thinking skills, waste cooking oil, project-based learning